Preliminary View on Journalistic and Intellectual Life of Mohammad Said (MS): A Discourse on Anti Colonial Struggle - Özay, Mehmet; Agustono, Budi (Journal of Al-Tamaddun, 2023)
This work probes the life history and journalistic career of Mohammad Said (1905-1995) in a condensed manner, with much consideration on intensive insight into his personality and writings. In this regard, this study can be classified as an example of microsociology because it departs from the general approach of conventional historiography by absorbing facts concerning grand political events and episodes. He was a self-made intellectual who explored in his writings formidable historical events concerning the migrant workers (koeli kontrak) in North Sumatra, and the Dutch War in Aceh. In addition, it was also pertinent to construct a framework to explain his ideas on the development of nationalism, and the factors that led to independence in the following decades. During the early 20th century, nationalism, identity, and nation-state were a patchwork, and had cleavages in many people’s minds in the Archipelago. Nevertheless, new discourses were developed to gain political consciousness and power through the writings of young journalists and intellectuals like Mohammad Said (MS). The thoughts and actions of MS should be considered as representing the values of his time. In this regard, one can assert that—in a Hegelian way—his self-consciousness helped the readers to comprehend the ‘spirit of the time.’ This study carried some glimpses of the era of tense discussions of independence, and anti-colonial struggles through MS’s intellectual discourse. This approach, namely viewing past political developments through the prism of a social agent, is essential.